Fear of Nurses During COVID-19 Pandemic in Saudi Arabia: A Cross-Sectional Assessment - Moussa, Mahaman L.; Moussa, Fatchima Laouali; Alharbi, Homood A.; Omer, Tagwa; Khallaf, Saleh Abdulkarim; Al Harbi, Hamad Samran; Albarqi, Ahmed Abdullah (Frontiers in Psychology, 2021)
Abstract Objective We aimed to assess the level of fear among nurses in Saudi Arabia during the COVID-19 outbreak. Methods A cross-sectional survey-based study was conducted from June to August 2020. All nurses currently working in public and private hospitals in Saudi Arabia during the COVID-19 pandemic were invited to complete an online survey. We used the 7-item unidimensional Fear of COVID-19 Scale (FCV-19S) to assess the level of fear of COVID-19. Multiple regression analysis was used to identify predictors associated with fear of COVID-19. Results A total of 969 nurses participated in the study. The participants were relatively young with a mean age of 35.5 ±10.46. About two-thirds of the participants were female (65.9%), married (57.2%) and were non-Saudi nationals (67%). The total mean score for the FCV-19S was 19.7 SD 7.03 (range 7 to 35) which near the mid-point, indicating a moderate level of fear of COVID-19. Of the eight variables measured in the analysis, three variables emerged as a significant predictor (gender, marital status and age). A higher level of fear (FCV-19S) was associated with being female, married and older age (p = <0.05). Conclusion Our study demonstrated the level of fear of COVID-19 among nurses in Saudi Arabia. Overall, Saudi nurses reported moderate levels of fear of COVID-19. Assessing the level of fear of nurses who work during the COVID-19 pandemic should be a priority to healthcare administrators to prevent mental health difficulties or psychological injury.